Readiness for self-directed learning among King Abdulaziz University medical students - Al-Basri, Samera Fahad; Al-Afari, Reem; Al-Hibshi, Amro M.; Al-Sayes, Faten; Soo, Park Yoon; Tekian, Ara (International Journal of Research in Medical Sciences, 2016)
Background: To determine readiness for self-directed learning (SDL) among medical students enrolled at King Abdulaziz University (KAU) in Jeddah, Saudi Arabia, as well as identify demographic characteristics that might affect or control such readiness. Methods: Medical students at all levels of training were asked to participate in a study in the form of a self-response questionnaire via emailed link (Gugliemino’s Self-Directed Learner Readiness Scale [SDLRS]). This instrument was designed to measure the complex attitudes, skills and characteristics that comprise an individual’s current level of readiness to manage his or her own learning. Data were analysed using SPSS, and mean, median and total scores were calculated and compared. Results: Of more than 1900 medical students at the KAU Faculty of Medicine, 192 students responded to the self-response questionnaire (see appendix). Results suggested that readiness for SDL is below average for more than 99% of medical students Conclusions: Our study showed that further evaluation of our students’ readiness for SDL is required, as well as exploration and implementation of tools for improving skill and knowledge development, to enable students to develop a lifelong learning attitude.